Lines in the snow; minor paths in the search for early childhood education for planatary wellbeing - Myrstad, Anne; Hackett, Abigail; Bartnæs, Pernille Elisabeth (Global Studies of Childhood, 2020)
This paper explores what place means for early childhood education at a time of global environmental precarity. We draw on fieldwork in Arctic Norway, where kindergarten children spend time with snow for more than half of the year. Children’s movement attunes to the nuances and diversity of the snow, as seasons, temperature, light, wind and weather change the consistency of snow and the possibilities for what can occur. The paper presents data of children walking in deep snow during an ice-fishing trip, a practice known as ‘grynne’, asking what we can learn both about the moment-by-moment attunement between child, snow and place necessary to grynne, and the paths of movement left behind in the snow afterwards. We draw on Manning’s work in order to trace the major and minor gestures running through grynne, as an analytic starting point for educators considering the role early years pedagogy might play in planetary sustainability.Thinking beyond the notion of humans as masterfully in control of environment, Ingold’s notion of correspondence offers a counter, advocating for a ‘lifetime of intimate gestural and sensory engagement’ as a way of learning to attune more deeply to place and take seriously the way in which place and humans mutually shape each other. In a place where seasonal temporality matters, in extreme ways that change how children’s bodies can move, we consider what children’s entanglement with snow can teach us, educators as well as researchers, about education for sustainability.